Clinical applications of patient-specific induced pluripotent stem cells in cardiovascular medicine. Issue 6 (27th January 2012) - Oh, Yingzi; Wei, Heming; Ma, Dongrui; Sun, Xiaoming; Liew, Reginald
Abstract : The emergence of induced pluripotent stem cell (iPSC) technology has had a great impact on the field of medicine ever since the ground-breaking discovery in 2006 that overexpression of four specific transcription factors was able to turn back the developmental clock of somatic cells into an embryonic-like state. The resulting iPSCs carry the developmental potential of human embryonic stem cells (hESC) without the embryo and have been heralded as a powerful tool to study development and disease. This technology has made it possible for the first time for researchers to transform end-differentiated cells from a particular individual into another cell type that remains specific to that individual, paving the way for novel methods of in vitro disease modelling and therapeutic applications. This paper reviews some of the key areas in cardiovascular medicine in which iPSC technology has been applied and discusses the future directions and ongoing challenges ahead in this exciting field.